Megaesôfago Idiopático Congênito em Cão. - Piovesan, Laís de Mato (Universidade Federal do Tocantins, 2023)
The purpose of this report is to describe the activities carried out during the Supervised Curricular Internship, in the period from March 11 to May 24, 2019, all of it, carried out at the University Veterinary Clinic of the Federal University of Tocantins, in the areas of medical clinic and surgical clinic of small animals, accounting for 424 hours, under the supervision of veterinarian Dr. Flavia Augusta de Oliveira and guidance of Dr. Andréa Cintra Bastos Torres Passos. In the course of the Internship, it was possible to follow the hospital routine, in its diversity and complexity, always in the presence of the Veterinary Doctors of the technical or teaching staff. In the clinical medical area performing the anamnesis, clinical and physical examination, collection of biological samples, medication administration, venous and curative access. In the surgical clinical area surgical procedures and monitoring of animals destined to this area, accompanying radiographic, ultrasonographic, echocardiographic examinations. In the area of hospitalization, as well as observation, assisting in the evaluation of vital parameters, in the definition of the medication and its administration. During the Internship it was possible to follow the Medical Clinic and surgical clinical sector, totaling 58 cases. In this report will also be reported a clinical case of Idiopathic Congenital Megaesophagus in dog, accompanied during the supervised stage.